Trends in osteoporosis-related fractures among the elderly in Kashan (2017-2021) - Khadijeh Kalanfarmanfarma; Esmaeil Fakharian; Mojtaba Sehat; Faezeh Asgari Tarazoj; Soudabeh Yarmohammadi (حیات)
Background & Aim: Osteoporosis is a common condition in the elderly, contributing to fracture incidence and associated pain. This study aims to analyze trends in osteoporosis-related fractures within the elderly population from 2017 to 2021. Methods & Materials: A descriptive cross-sectional study was conducted in 2024 involving 448 elderly people over 60 who experienced pelvic, hip, distal hand, or spinal injuries during 2017-2021 in Kashan. Data were extracted from the National Trauma Registry of Iran, including demographic information, injury severity, and frequency of fractures. The data were analyzed using analysis of variance and chi-square tests, with a significance level set at P<0.05. Results: Among the 448 participants, 244 were female (54.5%), with an average age exceeding 75 years among those diagnosed with osteoporosis. The most common fracture types included hip and pelvic fractures, affecting 331 individuals (73.9%), followed by distal hand fractures in 71 individuals (15.8%), and spinal fractures in 65 individuals (14.5%). The average injury severity score increased from 8.43±2.80 in 2017 to 8.96±2.77 in 2021. No significant changes were observed in the age distribution of the elderly population during this period; however, the proportion of males increased by approximately 6%. Conclusion: The study results indicate a rising trend in hip fractures among the elderly in Kashan. To reduce fracture incidence, it is recommended to implement proactive screening for osteoporosis risk factors in this population.